Pengaruh Nilai Kurs, Rentabilitas, Dan Tingkat Suku Bunga Terhadap Yield Obligasi Pada Perusahaan Manufaktur Yang Diperdagangkan Di Bursa Efek Indonesia Periode 2010-2013 - Kurniasari, Chandra Dewi; , Dr. Syamsudin, M.M (2016)
This study aims to determine the effect of variable Exchange Rate, profitability (Return On Equity and Return On Investment), and the Interest Rate on Yield Bond. The research sample represented 44 manufacturing companies that issue bonds and no losses and is listed on the Indonesia Stock Exchange (BEI) in the 2010-2013 period. According to the type of data that is required is secondary data that is both quantitative and methods of sampling using purposive sampling, data collection is based on the technique of the documentation presented by the library BEJ Surakarta Muhammadiyah University published by the Indonesian Capital Market Directory (ICMD) and Indonesia Bond Market Directory (IBMD), during the 2010-2013 period. The method of analysis used in this study with an analysis of the statistical description, classic assumption test including normality test, multicollinearity test, heterokesdatisitas test, and autocorrelation test. It also uses hypothesis testing using multiple regression analysis, t test, F test at a significant level, and the coefficient of determination. Variable Exchange Rate shows that the rate of negative and significant effect on bond yields. Variable profitability as measured by Return On Equity and Return On Investment shows that do not have a significant effect on bond yields. While variable interest rates indicate that interest rates positive and significant effect on bond yields. F test results showed that the rate / exchange rate, profitability and interest rates together significant effect on bond yields. Likewise, the coefficient of determination test results showed that the yield of bonds affected by the exchange rate, profitability and interest rate of 27.9%, the rest is influenced by other variables outside of this research model.